Methylation-induced silencing of maspin contributes to the proliferation of human glioma cells - XU, LIANG (Oncol Rep, 2016)
Maspin, a member of the serpin superfamily of serine protease inhibitors, has been reported to be involved in cancer initiation and progression. However, the expression of maspin and its expression regulation in glioma remain unknown. In the present study, we aimed to investigate the function of maspin in glioma cells and its regulatory mechanism. We found that the expression of maspin was silenced in glioma cells and tissues. Although maspin had no effect on the migration and invasion of human glioma cells in vitro, overexpression of maspin inhibited cell growth in U87 cells. We showed that the methylase inhibitor 5-Aza-2′-deoxycytidine induced the expression of maspin in glioma cell lines. Furthermore, both U87 and U251 cells showed hypermethylation in the maspin promoter. In addition, bisulphite sequencing analysis indicated that 16 CpG sites in the promoter were completely methylated in glioma cells and cancerous tissues, while CpG dinucleotides in the maspin promoter were unmethylated in normal brain tissues. Our data suggest that methylation-induced silencing of maspin contributes to the proliferation of human glioma cells, and maspin may be a potential therapeutic target in glioma.